A Magnetic‐Driven Switchable Adhesive Superhydrophobic Surface for In Situ Sliding Control of Superparamagnetic Microdroplets. Issue 1 (25th November 2021) - Hu, Dongdong; Lai, Hua; Cheng, Zhongjun; Song, Yingbin; Luo, Xin; Zhang, Dongjie; Fan, Zhimin; Xie, Zhimin; Liu, Yuyan
Abstract: Droplet manipulation plays an important role in many fields, and smart adhesion control on superhydrophobic surfaces is widely accepted as an effective strategy. However, some imperfections such as long response time and deformable elastic materials are still difficult to be avoided for existing methods. Herein, a new strategy is reported to reversibly control the surface adhesion and droplet's sliding without the change of surface chemistry and microstructure. A novel superhydrophobic surface is prepared by integrating a substrate with a certain size of NdFeB magnetic region and a hydrophobic SiO2 coating. The magnetic region on the surface is highly adhesive, which can pin a superparamagnetic droplet tightly. As an external magnet (EM) with opposite direction of magnetic flow to the NdFeB magnetic region is put above the droplet, the droplet rolls off as the surface is tilted, indicating that the high adhesive region has turned into the low adhesive state and in situ droplet's sliding control is realized. After removing the EM, the magnetic region on the surface can regain the high adhesion, demonstrating an excellent controllability. Finally, based on the smart controllability, the surface with several magnetic regions is designed and on‐demand storage/release control of different droplets is demonstrated. Abstract : The magnetic region on the surface has high adhesion state, which can pin a superparamagnetic droplet. As an external magnet (EM) is put above the droplet, it will roll off spontaneously as the surface is tilted, indicating that the high adhesive region has turned into the low adhesive state. After removing the EM, it regains the high adhesion.